ANALISIS STABILITAS KEUANGAN BANK SYARIAH: PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON-PERFORMING FINANCING (NPF), DAN FINANCING TO DEPOSITE RATIO (FDR) TERHADAP PROFITABILITAS BANK MUAMALAT INDONESIA PERIODE 2013-2024 - Ahmad Masyaril Fuadi; Achmad Raihan Rafli; Rizka Mauliddiana; Arya Ramadhani; Khusnul Fikriyah (JURNAL ILMIAH EDUNOMIKA, 2025)
This research examines the financial stability of Bank Muamalat Indonesia by analyzing the impact of the CAR, NPF, and FDR on the bank’s profitability, as measured by Return on Assets (ROA), over the 2013–2024 period. Employing a quantitative design with an associative causal framework, the study analyzes 48 quarterly observations derived from the formal financial reports of Bank Muamalat and the OJK. The dataset was processed using multiple linear regression supported by classical assumption diagnostics. Empirical findings reveal that CAR, NPF, and FDR jointly exert a significant impact on ROA, explaining 83% of the variation in profitability. On an individual level, CAR shows a positive yet statistically insignificant relationship with ROA, implying that adequate capital alone does not guarantee enhanced returns without efficient asset deployment. Conversely, NPF and FDR exhibit significant negative effects, indicating that rising credit risk and suboptimal fund allocation undermine profitability. These results highlight the necessity for Islamic banks to strengthen capital management, enforce prudent financing policies, and optimize liquidity strategies to sustain financial stability.